Some class of generalized entire sequences of Modal Interval numbers (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
The history of modal intervals goes back to the very first publications on the topic of interval calculus. The modal interval analysis is used in Computer graphics and Computer Aided Design (CAD), namely the computation of narrow bounds on Bezier and B-Spline curves. Since modal intervals are used in different fields, we have constructed a new sequence space  of modal intervals. Also , we have given some new definitions and theorems about the sequence space  of modal interval numbers.